دور عناصر المنظمة المتعلمة في تحقيق الابتكار التنظيمي دراسة ميدانية في جامعة تشرين - ديب كندة; البهلول علي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The research aims to examine the relationship between learning organization elements on the one hand, and between organizational innovation in Tishreen University on the other hand, the researcher distributed(175) questionnaire to a sample of the colleges in the Tishreen University, since that(134) responses were received, and(122) questionnaire were used in the analysis(response rate 91%). To test the relationship, the researcher used the Student T test for one sample, as well as the Pearson correlation coefficient. The research concluded that there is a decrease in the level learning organization elements in colleges under study, as well as a decrease in the level organizational innovation in colleges under study. The research concluded that there is significant relationship between learning organization elements and organizational innovation at Tishreen University, and thus the existence of the role of learning organization elements in the achieving of organizational innovation at Tishreen University. The research found a set of recommendations and proposals that will contribute positively in the role of learning organization elements in the achieving of organizational innovation. هدف البحث إلى دراسة العلاقة بين عناصر المنظمة المتعلمة من جهة، وبين الابتكار التنظيمي في جامعة تشرين من جهة ثانية، حيث قام الباحث بتوزيع استبانة على عينة من الكليات في جامعة تشرين بلغت (175) استبانة تم استرداد (134) استبانة منها، كان صالحاً منها للاستخدام(122) استبانة (بنسبة استجابة 91%). ولاختبار العلاقة قام الباحث باستخدام اختبار T ستيودنت لعينة واحدة، وكذلك معامل ارتباط بيرسون. توصل البحث من خلال الدراسة إلى أن هناك انخفاض في مستوى عناصر المنظمة المتعلمة في الكليات محل الدراسة، وكذلك انخفاض في مستوى الابتكار التنظيمي في الكليات محل الدراسة. كما توصل البحث إلى وجود علاقة معنوية بين عناصر المنظمة المتعلمة والابتكار التنظيمي في جامعة تشرين، وبالتالي وجود دور لعناصر المنظمة المتعلمة في تحقيق الابتكار التنظيمي في جامعة تشرين. وخلص البحث إلى مجموعة من التوصيات والمقترحات من شأنها أن تسهم بشكل إيجابي بدور عناصر المنظمة المتعلمة في تحقيق الابتكار التنظيمي.